Comparative effectiveness of individualized longer and standardized shorter regimens in the treatment of multidrug resistant tuberculosis in a high burden country - Wahid, Abdul; Ghafoor, Abdul; Khan, Abdul Wali; Al-Worafi, Yaser Mohammed; Latif, Abdullah; Shahwani, Nisar Ahmed; Atif, Muhammad; Saleem, Fahad; Ahmad, Nafees (Frontiers in Pharmacology, 2022)
Objective To compare the effectiveness of second line injectables containing a shorter treatment regimen (STR, duration 9-12 months) and longer treatment regimen (LTR, duration > 20 months) among multidrug-resistant tuberculosis (MDR-TB) with no documented resistance and history of treatment with any second-line anti-TB drug (SLD) for > 1 month. Methods This was an observational cohort study of MDR-TB patients treated at eight PMDT units in Pakistan. Patients' data from baseline until treatment outcomes were collected from Electronic Nominal Recording and Reporting System. The treatment outcomes of "cured" and "treatment completed" were grouped together as successful, whereas "death," "treatment failure," and "lost to follow-up" were collectively grouped as unsuccessful outcomes. Time to sputum culture conversion (SCC) was analyzed using the Kaplan–Meier method and the differences between groups were compared through the log-rank test. Multivariate Cox proportional hazards and binary logistic regression analyses were used to find predictors of time to SCC and unsuccessful treatment outcomes. A p-value <0.05 was considered statistically significant. Results A total 898 eligible MDR-TB patients (313 treated with STR and 585 with LTR) treated at eight centres in Pakistan were evaluated. Time to achieve SCC was significantly shorter in STR group (mean: 2.16 months, 95% confidence interval [CI]:1.92–2.41) than in LTR group (mean: 2.79 months, 95%CI: 2.51– 3.07) (p-value<0.001, Log-rank test). Treatment success was higher in STR (83.7%) than in LTR (73.2%) group (p-value <0.001) due to high cure (79.9% vs 70.9%, p-value=0.004) and low death (9.9% vs 17.4%, p-value=0.002) rates with STR. Treatment with STR emerged the only predictor of early SCC (Hazards ratio [HR] =0.825, p-value=0.020), whereas, patient’s age of 41-60 (odds ratio [OR]:2.26, p-value<0.001) and >60 years (OR=5.84, p-value<0.001), baseline body weight of 31-60 (OR=0.36, p-value=0.001) and >60 kilograms (OR=0.23, p-value <0.001), and treatment with LTR (OR=1.88, p-value=0.001) had statistically significant association with unsuccessful treatment outcomes. Conclusion STR exhibited superior anti-microbial activity against MDR-TB. When compared LTR treatment with STR, STR resulted in significantly early SCC, high cure, and lower death rates among MDR-TB patients who had no documented resistance and history of treatment with any SLD > 1 month.